Peningkatan Kesadaran Kesehatan dan Keselamatan Kerja di Lingkungan GPIB Filadelfia Semarang - Sola Wina Gracia Sinaga; Monica Cintya Butarbutar; Diaz Putra Pratama (Yayasan Sumber Daya Manusia Cerdas, 2024)
Occupational Safety and Health (OSH) is a crucial element in creating a safe, healthy, and productive work environment. This study aims to promote the importance of OSH implementation at the Protestant Church in Western Indonesia (GPIB) Filadelfia Congregation, Semarang. The methods employed in this community service activity include intensive coordination with partners, the development of OSH modules, the provision of basic OSH equipment, and the execution of awareness campaigns. The findings reveal that the partners require equipment such as fire extinguishers, evacuation signs, safety helmets, and fire blankets to support building renovation activities and daily operations. Additionally, the OSH module developed covers risk management, planning, and the implementation of procedures tailored to the partner's needs. The awareness campaigns successfully enhanced the partners' understanding of the importance of OSH and its practical application. This initiative is expected to serve as a model for OSH implementation in non-industrial environments to minimize workplace accidents and promote collective safety.